Determinants of agricultural machinery adoption intensities in Ghana - Takeshima, Hiroyuki; Liu, Yanyan (International Food Policy Research Institute, 2019)
Increased capital use in agriculture, including mechanization, is con-sidered an integral process of agricultural transformation. Despite some recent emergence of medium-to-large scale farmers in SSA, as well as labor-movement out of agricultural sector (particularly youths), smallholders without substantial mechanization have re-mained the majority in the agricultural sector in countries like Gha-na. Globally, mechanization has often been associated with large-scale farming given the complementarity between machine and land. The experiences in Asia in the last few decades, however, suggest that mechanization may grow even among smallholders before they transition into larger-scale farmers. These experiences have prompted the need to understand better how mechanization may be adopted by smallholders for whom the scope for exploiting complementarity between mechanization and land is limited. We test the hypotheses that high-yielding technologies, which potentially raise returns to more intensive farm power use, are im-portant drivers of adoptions of agricultural mechanization among smallholders at both extensive and intensive margins. We do so using the three rounds of repeated cross-sectional, nationally rep-resentative data (Ghana Living Standard Surveys (GLSS) 2006, 2013, 2017), as well as unique tractor-use data in Ghana collected by IFPRI and Savannah Agricultural Research Institute (IFPRI-SARI data), and multi-dimensional indicators of agroclimatic similarity with plant-breeding locations.